2013
DOI: 10.1103/physreva.87.043823
|View full text |Cite
|
Sign up to set email alerts
|

Controlled transportation of mesoscopic particles by enhanced spin-orbit interaction of light in an optical trap

Abstract: We study the effects of the spin orbit interaction (SOI) of light in an optical trap and show that the propagation of the tightly focused trapping beam in a stratified medium can lead to significantly enhanced SOI. For a plane polarized incident beam the SOI manifests itself by giving rise to a strong anisotropic linear diattenuation effect which produces polarization-dependent off-axis high intensity side lobes near the focal plane of the trap. Single micron-sized asymmetric particles can be trapped in the si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Thus, in the matter of choice of inorganic materials for such purpose we required materials that were responsive to physical perturbations, had soft interfaces, and were also reactive to light. We have previously shown that under optical field we can induce responsive motion with a class of soft mesoscopic objects and even induce phase transitions in them 2022. Such soft materials are known as soft‐oxometalates (SOMs) 23–25.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the matter of choice of inorganic materials for such purpose we required materials that were responsive to physical perturbations, had soft interfaces, and were also reactive to light. We have previously shown that under optical field we can induce responsive motion with a class of soft mesoscopic objects and even induce phase transitions in them 2022. Such soft materials are known as soft‐oxometalates (SOMs) 23–25.…”
Section: Introductionmentioning
confidence: 99%
“…We have discussed how the induced polarization and alignment of diatomic molecules due to linearly polarized intense laser field can be useful for experimental verification of our theory. The alignment and orientation of the molecules of nematic liquid crystal have been found to play an important role in OAM transfer [51][52][53][54], indicating that similar effects in gas phase molecules in intense laser fields will be important for light OAM transfer to the molecules. Finally, the recent advent of ultra long-range cold Rydberg molecules whose electronic orbital can be as large as 100 nm [55,56] and the demonstration of the alignment of such molecules [57] open a new avenue for studying OAM transfer in light-molecule interactions with huge enhancement of the size effects for the ability of the molecular electrons to experience the spatial variation of light intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Light OAM will be nearly a good quantum number under paraxial approximation only. In recent times several experiments [50][51][52][53][54] have demonstrated the transfer of angular momentum in light-matter interactions through spin-orbit interactions or inter-conversion between spin and angular momenta of photons in different physical systems, for example, in nematic liquid crystal [51][52][53] and nanoplasmonics [50,54]. The transfer of angular momentum in interaction of light with nematic liquid crystal is quite interesting.…”
Section: Quadrupole Interaction Of a Bec With An Lg Beam: Numerimentioning
confidence: 99%
“…It has been shown by us and others that each of the components of the above host-guest species [PMo 12 @Mo 72 Fe 30 ] i.e., PMo 12 and Mo 72 Fe 30 independently shows superstructured soft-oxometalate (SOM) formation by spontaneous assembly in colloidal lengthscales. 1,2,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We have previously shown that a dilute sonicated dispersion of PMo 12 leads to the formation of peapod 37 like SOM structures. Initially, the peapods have nanosphere-type morphology and with time these spheres get converted to nanorods with nanospheres embedded inside this rod.…”
Section: Introductionmentioning
confidence: 99%